'Réformez vos contrats!': From the Marriage Contract to the Social Contract in Louise Dupin and Jean-Jacques Rousseau. Issue 1 (2nd January 2021) - Wilkin, Rebecca
Abstract : I trace key arguments of Jean–Jacques Rousseau's political philosophy to Louise Dupin's Ouvrage sur les femmes to reveal that early modern feminist thought contributed directly to social contract theory . Rousseau applied Dupin's mockery of the marriage contract to dismiss as fraudulent the political contract that previous natural law philosophers had imagined between subjects and sovereign. He then made mutually exclusive property the foundation of the republican social contract, just as Dupin had stipulated separately owned property as the condition of equality in marriage. Yet Rousseau rejected the feminist content of Dupin's arguments, despite incorporating her strategies. Paradoxically, while Dupin, a monarchist, construed marriage along the egalitarian lines of a friendship based on 'la douceur du commerce', the republican Rousseau invested men with the douceur of the absolute sovereign, masking the contractual character of marriage by positing women's subordination to men as a matter of passionate attachment.